The model of evidence-based benchmarking: a more robust approach to benchmarking. Issue 2 (10th November 2020) - Kulikowski, Konrad
Abstract : Purpose: This conceptual paper aims to propose the evidence-based benchmarking model that bridges standard benchmarking practices with evidence-based management (EBMgt) principles and lessens tensions between two opposite views of benchmarking as a useful management tool vs a management hype and fashion. Design/methodology/approach: This conceptual paper is based on the critical reasoning, analysis and integration of so far largely separated research fields of benchmarking and EBMgt. The author employs a method of conceptual model building to identify connections between standard benchmarking model and EBMgt practices and to explain how a sequence of benchmarking events supplemented by EBMgt principles might lead to more reliable managerial decision-making. Findings: The author argues that although there are no common benchmarking procedures, it is possible to identify a standard benchmarking model that resonates in most contemporary benchmarking procedures and consists of four main phases: plan, do, check and act (PDCA). The author integrated this standard model with EBMgt practices of searching for evidence in four sources of information and a six-step critical thinking process to put forward the model of evidence-based benchmarking. Originality/value: The proposed model is a novel, comprehensive framework that puts together so far incompatible practices of benchmarking and EBMgt. The model clears up existing conceptual confusions around "casual" benchmarking and advances contemporary understanding of benchmarking practices. The model of evidence-based benchmarking might act as a practical, heuristic tool improving the quality of the managerial decisions and thus positively influencing the bottom line of business performance.